THE INFLUENCE OF GEOGRAPHIC LOCATION AND ENZYME-ASSISTED EXTRACTION ON ESSENTIAL OILS COMPOSITION OF THYMUS SERPYLLUM GROWING WILD IN TRANSYLVANIA - GOJA, Ioana; ULICI, Adelina; CULEA, Monica; MUNTEANU, Vasile; PODEA, Paula (Studia Universitatis Babeș-Bolyai Chemia, 2020)
A comparative study concerning the influence of geographic location and also the influence of enzyme-assisted extraction on the essential oils isolated from Transylvanian wild Thymus serpyllum was achieved. The collected Thymus serpyllum plants, from three different regions from Transilvania, were hydrodistilled to yield essential oils. The influence of enzymatic assisted extraction on the essential oils isolated from Thymus serpyllum was evaluated. All analyzed plants proved to belong to carvacrol chemotype class. The major constituents of wild Thymus serpyllum from these three regions were carvacrol (26.58%-47.62%), p-cymene (8.61%-18.97%), methylcarvacrol (8.81%-13.35%), thymol (1.6%-11.07%), gamma-terpinene (2.09%-7.55%), beta-bysabolene (3.42%-5.18%), caryophyllene (3.17%-4.83%). Using the enzymatic treatment, the percentage in composition of some components was modified and proved to have an improvement on antioxidant and antimicrobial properties. All studied essential oils exhibited considerable antioxidant and antimicrobial activity.